The Livingstone Museum and its role in postcolonial Zambia, 1964-2006 (Historia, 2021)
The first article on the Livingstone Museum, published last year in Historia, demonstrated that the Museum was originally established as a tool to exhibit African material culture in order to provide evidence to the rest of the world of the superiority of European culture compared to African culture. The article argued that this was because European settlers saw the need to legitimise colonial rule in the territory; colonial officials felt that the "civilising" effect of European culture was necessary to rescue Africans from their "primitive" way of life. This piece examines the Livingstone Museum and the role it played in independent Zambia, from 1964 to 2006. With the aid of temporary and permanent exhibitions mounted at the institution during this period, the article postulates that in the same vein as the colonial administration, the postcolonial government also used the Museum as a tool to promote its political agenda. Its main objective was to reverse the negative image that the Zambian culture and history had been accorded in the colonial period. The Museum was used as an ally by the nationalist government to promote national unity and patriotism, which had been undermined during the colonial era. In order to achieve this objective, the Museum staged exhibitions that glorified the African people and their culture at the expense of other racial groups that had emerged following colonial rule, such as Europeans and Indians. This article advances the thesis that contrary to the slogan "one Zambia one Nation", advanced by politicians after the attainment of independence (with the aim of creating a Zambian society in which all racial groups live in harmony) the Livingstone Museum's presentations in postcolonial Zambia were not balanced but were decidedly Afrocentric. In other words, postcolonial Livingstone Museum was also guilty of racial prejudice - the very same offence of which the colonial Museum was accused when they mounted their Eurocentric presentations. In practical terms, the Museum's exhibitions in each period reflected the current political dispensation. They were Eurocentric in the colonial period and Afrocentric in the postcolonial period. Nevertheless, the Museum does offer a platform, an educational centre through which both Zambian and foreign visitors are able to learn the country's culture, history, natural history and it indicates the path that the Zambian people have traversed from pre-colonial times to the present. Above all, it has kept alive the rich Zambian historical and cultural heritage.  Die eerste artikel oor die Livingstone Museum, gepubliseer in 2011 in Historia, het bewys dat die museum gestig is omruimte te skep vir die uitstalling van die materiele kultuur van Afrika om sodoende bewys te lewer aan die wêreld dat die Europese kultuur meerderwaardigheid is wanneer dit met dié van Afrikane vergelyk word. Die argument in die artikel was dat dit genoodsaak was deur die Europese setlaars se behoefte om hul beheer oor die area te legimiteer. Koloniale amptenare het dit gesien as 'n noodsaaklikheid om deur die "beskawende effek" van Europesekultuur Afrikane te red van hul "primitiewe" leefwyse. Hierdie artikel ondersoek die Livingstone Museum en die rol wat dit gespeel het in onafhanklike Zambie vanaf 1964 tot en met 2006. Met die hulp van tydelike en permanente uitstallings wat tydens die periode by die museum gemonteer is, postuleer die artikel dat net soos die koloniale owerhede voorheen, het die postkoloniale owerheid die Livingstone Museum ook gebruik as 'n medium om hul agenda te bevorder - naamlik 'n ommekeer van die negatiewe beeld wat Zambie se kultuur en geskiedenis gebuk gegaan het onder kolonialisme. Die museum is gesien as 'n bondgenoot van die nasionalistiese regering in die se strewe om patriotisme en nasionaleeenheid te bevorder wat tydens die koloniale periodeondermyn was. Om die doelwit te bereik het die museum uitstallings opgerig tot die glorie van Afrikane en hul kultuur ten koste van ander groepe soos blankes en Indiers. In hierdie artikel word daar geargumenteer dat die slagspreek "one Zambia one Nation", wat na die verkryging van onafhanklikheid deur politici gebruik om 'n Zambiese gemeenskap waarin allegroepe in harmonie kon saamleef nie bereik is deur die postkoloniale uitstallings van die Livingstone Museum nie omdat dit uiteraard Afrosentries was. Om dié rede was die postkoloniale Livingstone Museum skuldig aan dieslefde rassevooroordeel waarvan die koloniale museum en die se Eurosentriese uitstallings beskuldig was. Derhalwe, reflekteer die museum se uitstallings die politiek van die dag - Eurosenties tydens die koloniale era en Afrisentries tydens die postkoloniale era. Nieteenstaande bied die museum 'n platform en 'n opvoedkundige sentrum waar beide die Zambiese en buitelandse besoekers kon leer oor die geskiedenis, kultuur, en die pad wat die mense van Zambie gewandel het vanaf die prekoloniale tydperk tot die huidige. Bowen alles het die museum die ryke geskiedenis en kulturele erflating van die mense van Zambie lewendig gehou.
Keywords: Colonial period; Eurosentries rassevooroordele; Een Nasie; Zambie; Afrocentric political agenda; Een Zambie; Educational centre; Colonialism; Onafhanklikheid; Material culture; Eurocentric racial prejudice; Postkoloniale periode; Kolonialisme; Zambia; One Zambia; Postcolonial period; Materiele kultuur; Koloniale periode; One Nation; Afrosentries politieke agenda; Opvoedkundigesentrum; Livingstone Museum; Independence